Contextualization of professional training of future teachers: reflexive dimension - Zhelanova Victoria (Borys Grinchenko Kyiv Metropolitan University, 2015)
This article presents contextualization of professional training for future teachers as an important principle of the modern higher education. The author describes three dimensions of this phenomenon: conceptual, contextual and managerial one. The research explains that conceptual part is based on the reflexive and contextual scientific approach, principles of meaningful, subjective, reflexive commitment of training, on understanding professional context of future teachers as integration of motivational and inspiring, reflexive and forming, sense producing, subjective forming, communicative forming professional contexts. Contextual aspects of professional training for future teachers are connected with integral professional experience interiorization of which takes place during process of motives transformation as well as reflexive genesis, sense genesis, subjective genesis. Managerial part of contextualization of professional training is aimed at implementing managerial forms of training into such as lectures of contextual type, business games, pedagogical tasks of contextual direction. The author proves that practical realization of contextualization principle is related to implementation of points of reflexive and contextual scientific approach which is combination of reflexive educational paradigm and ideas of contextual education. The author proves that the aim of professional training within the scope of reflexive and contextual scientific approach is formation of reflexive competence, and reflexively determined constructs of future teachers which are motivational, sense spheres of personality and its professional subjectivity.